Chilean Antarctic Statute and Environmental Impact Assessment: regulatory considerations to protect the Antarctic environment and its dependent and associated ecosystems - Currie Ríos, Robert; Sandoval Valdés, Paulina (Revista Tribuna Internacional, 2021)
The Protocol to the Antarctic Treaty on Environmental Protection compels the Parties to the global protection of the Antarctic environment and dependent and associated ecosystems. Additionally, it includes an annex on Environmental Impact Assessment (EIA) requiring that the environmental impact of activities carried out in Antarctica are considered, before their commencement, in accordance with appropriate national procedures. In this context, our article addresses how EIA has evolved internationally and how the Chilean Antarctic Statute integrates international guidelines on the matter. Likewise, we reflect on the interactions between Antarctic and national EIA, highlighting their differentiating elements. Finally, we propose some elements to consider when regulating Antarctic EIA, particularly in relation to international guidelines and commitments.